Gottfried Ostermeyer’s Manual Inscriptions in the Copy of His Book Erste Littauische Liedergeschichte (1793) at Göttingen State and University Library, Lower Saxony - Aleknavičienė, Ona; Šinkūnas, Mindaugas (Senoji Lietuvos literatūra, 2016)
This paper deals with the circumstances of Erste Littauische Liedergeschichte (The First History of Lithuanian Hymns, Königsberg, 1793) by Gottfried Ostermeyer, an Evangelical Lutheran pastor of Trempai (Darkiemis district) finding its way to Göttingen State and University Library, Lower Saxony (Niedersächsische Staats- und Universitätsbibliothek Göttingen; SUB Göttingen: 8 H L BI I, 8856). Manuscript inscriptions in this copy are identified and their nature is evaluated. It provides some information on the history of the library and its collection of sixteenth-to-nineteenth-century books related to Lithuanian studies. On the basis of a 1798 review of Osterneyer’s book Erste Littauische Liedergeschichte (1793) in Göttingische Bibliothek der neuesten theologischen Literatur (Göttingen, 1798, vol. IV, part I) published by Karl Friedrich Stäudlin, it has been established that Ostermeyer personally sent one copy of the book to Göttingen. He might have done it in 1797. Karl Friedrich Stäudlin is considered the reviewer (the review is undersigned by the initial S; see ‘Publikacijos’ section for its facsimile copy and translation into Lithuanian). From Ostermeyer’s letter mentioned in the review it becomes clear that the author himself funded the publishing of the book and that it was not on sale. It is very likely that Ostermeyer sent the book to Göttingen with the hope that it would be reviewed and that information about Lithuanian hymns and studies into their history would spread beyond the boundaries of Lithuania Minor. As a member of the Royal German Society in Königsberg, he took care of the dissemination of his scholarly studies and therefore indicated the possible ways of the distribution of his book to foreign readers. Manuscript inscriptions made by Ostermeyer in black ink are of two types: additions (in the margins) and error corrections (in the text and in the margins). Bearing in mind that Ostermeyer indicated the date of the ordination of his son, Siegfried Ostermeyer, as 24 July 1795, and the reviewer’s reference to the time of the arrival of the book in Göttingen (‘im vorigen Jahre’, in the previous year), the manuscript inscriptions should be dated between 1795 and 1797. Corrections of errors point to Ostermeyer’s intolerance to inaccuracies and the thoroughness with which he approached not only texts written by others, but also the quality of his own writing.